2018
DOI: 10.1111/bcpt.13121
|View full text |Cite
|
Sign up to set email alerts
|

Porcine cytochrome 2A19 and 2E1

Abstract: Cytochrome P450 (CYP) is a major group of enzymes, which conduct Phase I metabolism. Among commonly used animal models, the pig has been suggested as the most suitable model for investigating drug metabolism in human beings. Moreover, porcine CYP2A19 and CYP2E1 are responsible for the biotransformation of both endogenous and exogenous compounds such as 3-methylindole (skatole), sex hormones and food compounds. However, little is known about the regulation of porcine CYP2A19 and CYP2E1. In this MiniReview, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…CYP2A19 transcription is controlled by the CAR transcription factor [ 78 ]. Its human orthologue, CYP2A6 is controlled by CAR, PXR, glucocorticoid receptor (GR), estrogen receptor HNF 4 , and PGC-1 α [ 79 ]. Also, the constitutive hepatic expression of CYP2A6 in mice is governed by an interplay between HNF 4 , CCAAT-box/enhancer binding protein (C/EBP , C/EBP and octamer transcription factor-1 (Oct-1) [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP2A19 transcription is controlled by the CAR transcription factor [ 78 ]. Its human orthologue, CYP2A6 is controlled by CAR, PXR, glucocorticoid receptor (GR), estrogen receptor HNF 4 , and PGC-1 α [ 79 ]. Also, the constitutive hepatic expression of CYP2A6 in mice is governed by an interplay between HNF 4 , CCAAT-box/enhancer binding protein (C/EBP , C/EBP and octamer transcription factor-1 (Oct-1) [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…In pig kidney, the expression of CYP2A19 is lower compared to that found in liver [ 79 ]. Probably due to this lower expression, animal exposure to the mixture of grapeseed and sea buckthorn meal generated an upregulation of Nrf-2 induced CYP2A19 gene expression due to the luteolin [ 85 ] and ferulic acid [ 86 ] content.…”
Section: Discussionmentioning
confidence: 99%
“…diet, (un)controlled housing conditions etc. ), and to breed-related genetic variations (Burkina et al, 2019). In humans, however, the CYP2E1 ontogeny pattern shows a gradual postnatal increase, specifically from the first month of life until 1 year of age (Vieira et al, 1996;Johnsrud et al, 2003).…”
Section: Cyp Protein Abundance Ontogeny Profilesmentioning
confidence: 99%
“…In the present study, these three CYPs were significantly up-regulated in SNT and LZT livers, suggesting that high-altitude environments are more prone to toxin production, which in turn induces toxicological responses in animal livers. Some studies have reported that CYP2E1 is most abundant in adult pig liver tissue and is able to metabolize many drugs and environmental toxins, playing a key role in the detoxification chain [ 26 , 27 ]. UGTs are a phase-II-specific family of enzymes that are capable of coupling and accelerating the metabolism of drugs and toxins.…”
Section: Discussionmentioning
confidence: 99%